Fixed Bed Column Adsorption System for the Removal of 2,4-Dichlorophenoxyacetic Acid Herbicide from an Aqueous Solution - Yalemtsehay Debebe; Zemene Worku; Esayas Alemayehu (Journal of Engineering)
The intensive use of 2,4-dichlorophenoxyacetic acid (2,4-D) herbicide has resulted in the presence of its residues in the environment, which leads to contamination of surface and groundwater. In this study, a fixed-bed column experiment was conducted for the removal of 2,4-D from an aqueous solution using termite mound soil (TMS). Scanning electron microscopy (SEM), Fourier transform infrared (FTIR), atomic absorption spectrometry (AAS), and Brunauer–Emmett–Teller (BET) techniques were used to characterize the adsorbent. The effect of significant variables, such as the initial 2,4-D concentration (50 mg/L and 75 mg/L), flow rate (2.5 ml/min and 5 ml/min), solution pH (2, 4, and 6), and bed height (3, 6, and 9 cm), on the breakthrough characteristics of the adsorption system was assessed. In addition, the Thomas and Yoon–Nelson models were applied to predict the breakthrough curves and to determine the characteristic parameters of the column that are useful for process design. The findings showed that at a lower pH (2), a lower flow rate (2.5 ml/min), a lower 2,4-D concentration (50 mg/L), a higher bed depth (9 cm), and 840 min breakthrough time, a higher removal percentage (80.2%) of 2,4-D was achieved. The experimental data were in good agreement with the Thomas and Yoon–Nelson models. For the Yoon–Nelson model, the rate constant increased with an increase in the flow rate, initial ion concentration, and bed height. The time required for a 50% breakthrough decreased with an increase in the flow rate, bed height, and initial ion concentration. For the Thomas model, the rate constant increased with an increase in the flow rate but decreased with an increase in bed height and initial concentration. Overall, the study showed that termite mound soil in a fixed-bed column adsorption system presents an excellent potential for removing 2,4-D from aqueous solutions.